ABOUT 3MF FILE FORMAT FOR 3D PRINTING - Cătălin IANCU (Fiabilitate şi Durabilitate)
In this paperwork is presented a documentary research regarding 3MF file format for 3D printing, the situation existing in the end of 2018 and early 2019, in comparison with other used file formats for this purpose, like STL, OBJ and AMF. There are presented also some characteristics of 3MF format, some limitation and the future perspective of this file format.